Pengembangan Media Interaktif Berbasis Android pada Mata Pelajaran Ekonomi - Elfrida Anjar Fitriyah; Retno Mustika Dewi (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
This research was conducted because teaching aids in the form of media used by teachers during learning activities were still relatively few. The purpose of this research is to assess the level of feasibility, effectiveness (learning outcomes) and practicality (response). In this development research, the test subjects were 20 students of class X IPS SMAN 1 Taman. The results of the research on the development of android-based interactive media were declared feasible with an average score of 79.9%, the effectiveness level of interactive media obtained an N-Gain score of 0.724 with a very effective category and a practicality level of 85% with very practical criteria.